Acculturation and wellness of native american adolescents in the United States of North America - Garrett, Michael Tlanusta; Torres Rivera, Edil; Dixon, Andrea L.; Myers, Jane E. (UANL Facultad de Trabajo Social y Desarrollo Humano, 2009)
Cultural conflicts and the process of acculturation contribute to feelings of boredom, anxiety, depression, isolation, stress, self-doubt, alienation, and rejection among Native American high school students. Further, acculturation may have a negative impact on the identity development and wellness of these students. The purpose of this pilot study was to: (a) assess and compare the levels of acculturation of Native American and non-Native American 9th, 10th, 11th, and 12th grade students; and (b) examine the relationship between level of acculturation and wellness for the Native American students. Results indicated significant differences between Native American and non-Native American students’ levels of acculturation; and significant differences between the Native students’ three levels of acculturation on some of the 17 scales of wellness.